Online resources as a source of information for exercise and physical activity in solid organ transplant recipients - Da Silva, Tania; Momen, Rozhan; Al Kaabi, Noor; Masrur, Muhib; Holdsworth, Sandra; Prevost, Karina; Logan, Sherrie; Santa Mina, Daniel; Mucsi, Istvan; Bhat, Mamatha; Alba, Ana Carolina; Reid, W. Darlene; et al. (Frontiers in Sports and Active Living, 2024)
Introduction Exercise training post-transplant has been shown to improve physical function and quality of life in solid organ transplant (SOT) recipients. Online resources in the form of websites and videos are commonly used to provide education and instruction on exercise and physical activity in SOT; however, the content and quality of these online resources has not been evaluated. Methods The first 200 websites and videos identified on Google and YouTube using the English search term “exercise and physical activity in solid organ transplantation” were analyzed. Website and video content was evaluated based on 25 key components of exercise and physical activity in SOT as described in established exercise program recommendations. Website and video quality was determined using DISCERN, Global Quality Scale (GQS), and Patient Education Materials and Assessment Tool (PEMAT; threshold for which material is deemed understandable or actionable is >70%). Parametric and non-parametric tests were used to assess website and video characteristics, content, and quality metrics. Results Forty-nine unique SOT websites (n = 15) and videos (n = 34) were identified, with the two most common categories being foundation/advocacy organizations and scientific resources. The average reading grade level of websites was 13 ± 3. Website and video content scores varied significantly (websites 11.3 ± 6.4; videos 8.4 ± 5.3). DISCERN total score and GQS score were low (median range for DISCERN 2.5–3.0; median for GQS 2.0 for both websites and videos, out of 5). PEMAT understandability and actionability scores were also low across websites and videos (mean range 57%–67% and 47%–65%, respectively). Foundation/advocacy websites had higher content and quality scores compared to scientific organizations and news/media articles. Conclusions To our knowledge, this is the first comprehensive assessment of online content and quality of website and video resources on physical activity and exercise in adult SOT recipients. There were a limited number of online English patient-directed resources related to physical activity in SOT, most of which only partly captured items outlined in consensus exercise program recommendations and were of low quality and understandability and actionability. This work provides important insight to the English-speaking transplant community on the current state of online exercise health information and provides future direction for resource development.